HUBUNGAN ANTARA KEMAMPUAN CRITICAL THINKING DENGAN HASIL BELAJAR CODING SISWA PADA MATA PELAJARAN INFORMATIKA KELAS X SMA KRISTEN CITRA BANGSA MANDIRI KUPANG - Evander Taneo, Rizaldy; Yanni Ariswati Fallo, Diana; Magdalena Beatrice Sogen, Maria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has increased the importance of critical thinking skills in Informatics learning, particularly in coding, which requires students to analyze problems, design algorithms, and evaluate program solutions. This study aimed to determine the relationship between students' critical thinking skills and their coding learning outcomes in the Informatics subject among tenth-grade students at SMA Kristen Citra Bangsa Mandiri Kupang. This research employed a quantitative correlational design involving 40 students selected as the research sample. Data were collected using a critical thinking questionnaire and coding achievement tests, then analyzed through descriptive statistics, normality testing, Pearson Product Moment correlation, and coefficient of determination using IBM SPSS Statistics. The findings revealed that students' critical thinking skills were generally in the moderate category with a mean score of 79.58, while coding learning outcomes were also in the moderate category with a mean score of 69.75. Pearson correlation analysis indicated a positive and significant relationship between critical thinking skills and coding learning outcomes (r = 0.501; p = 0.001 < 0.05), indicating a moderate level of correlation. The coefficient of determination showed that critical thinking contributed 25.1% to students' coding learning outcomes, while the remaining 74.9% was influenced by other factors beyond the scope of this study. Therefore, improving students' critical thinking skills is expected to support better coding learning outcomes in Informatics education